Buckling of composite columns - Syed Mohamed Ali, Jaffar; Jamaludin, Nur Faizlin; Roslan, Rosfarisya; Abdul Rahman, Mohammad (IIUM Press, 2011)
This chapter deals with the experimental procedure to evaluate the critical load, failure load and predict the mode of failure for the column speciments made of composite material. The type of section that is being considered is rectangular and both woven roving fiber and chopped strand mats fiber types of glass fibers have been examined.